National trauma and substance use disorders: A slippery slope in Lebanon. Issue 3 (3rd July 2021) - Bizri, Maya; El Hayek, Samer; Beaini, Hadi; Kobeissy, Firas; Talih, Farid
Abstract: Lebanon, a small middle-income nation in western Asia, has been crippled by decades of political turmoil and armed conflict. A "quadruple crisis" hit the country over the past years, starting with the protracted humanitarian Syrian refugee crisis, followed by a severe socioeconomic collapse, the global COVID-19 pandemic, and lastly the Beirut port catastrophic blast. With the exposure to repetitive traumatic events and associated organic brain injury, the Lebanese population has become at a higher risk of addiction, among other psychiatric comorbidities. With the scarce statistics about the topic and limited addiction services in the country, collaborative local efforts and international help are urgently needed to fight the upcoming substance use epidemic. Raising awareness, providing adequate training, and securing resources for the management of both addiction and trauma are of utmost importance.